Here u go: D. integer, B.Rational and C. real
Answer: 235,000,000
Step-by-step explanation:
Answer:
Jay started with $148.5 and Kay with $24.75.
Step-by-step explanation:
With the information provided you know that Jay had 6 times as much money as Kay wich can be expressed as:
J=6K, where
J is the money Jay had
K is the money Kay had
Also, you know that Jay gave Kay $33 and Jay now has twice as much money as Kay, which would be:
J-33=2(K+33)
Now, you can replace J=6K in this equation and solve for K:
6K-33=2K+66
6K-2K=66+33
4K=66
K=24.75
Then, you can replace the value of K in J=6K:
J=6*24.75
J=148.5
According to this, the answer is that Jay started with $148.5 and Kay with $24.75.
Answer:
The answer to your question is: ( - 24 / 29, ∞ )
Step-by-step explanation:
6x + 3 < 8 (8x + 6) + 3
6x + 3 < 64x + 48 + 3
6x + 3 < 64x + 51
6x - 64x < 51 - 3
- 58 x < 48
x > - 48 / 58
x > - 24 / 29
( - 24 / 29, ∞ )
Answer:
Step-by-step explanation: I have no idea